2018
DOI: 10.1039/c8nr04041a
|View full text |Cite
|
Sign up to set email alerts
|

Transient and flexible polymer memristors utilizing full-solution processed polymer nanocomposites

Abstract: Building transient and flexible memristors is a promising strategy for developing emerging memory technologies. Here, a transient and flexible memristor based on a polymer nanocomposite, with a configuration of silver nanowire (AgNW)/citric acid quantum dot (CA QD)-polyvinyl pyrrolidone (PVP)/AgNW, is fabricated using a full-solution process method. The obtained device exhibits reversible resistive switching behavior and a dynamic random access memory (DRAM) storage feature, with the significant merits of a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…[1][2][3][4] Building polymer memory devices with low resistive switching voltage hold great importance in their fundamental study as well as the technical advancement of ultra-low power memory devices during their practical 3D integration. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously.…”
Section: Doi: 101002/aelm201800503supporting
confidence: 89%
See 1 more Smart Citation
“…[1][2][3][4] Building polymer memory devices with low resistive switching voltage hold great importance in their fundamental study as well as the technical advancement of ultra-low power memory devices during their practical 3D integration. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously.…”
Section: Doi: 101002/aelm201800503supporting
confidence: 89%
“…Building polymer memory devices with low resistive switching voltage hold great importance in their fundamental study as well as the technical advancement of ultra‐low power memory devices during their practical 3D integration . To date, enormous efforts have been devoted to the rational design of memristive materials and their property studies, especially the achievement of Flash, write‐once‐read‐many times (WORM), and dynamic random access memory (DRAM) memory effect . However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously .…”
supporting
confidence: 65%
“…As MQDs are gradually released from the active film into water and PVP film is dissolved in water due to the formation of hydrogen bonds between water molecules and polar side groups of PVP, the intensity of blue light from culture dish becomes stronger owing to intrinsically blue emission of MQDs under UV irradiation and increasing concentration of MQDs in solvent, and the active film completely disappeared after 600 s, which is consistent with our previous reported transient electronics. [34] This transient feature provides a new insight into emerging memory device for data storage security and green electronics.…”
mentioning
confidence: 96%
“…The distribution and concentration of additives in the blend memory material has a signicant inuence on the reversibility or volatility of the lm resistor. 16 To date, inorganic nanomaterials, including metal NPs, 17,18 metal oxide NPs, 19,20 suldes, 21,22 and carbon materials, [23][24][25] have been widely investigated as a active layers of RRAM. Among these inorganic nanoparticles, n-type semiconductor ZnO NPs have attracted extensive attention due to their wide band gap (3.37 eV), strong electron mobility ($120 cm 2 V s À1 ), high excitation binding energy (60 meV), high melting point, excellent chemical stability, and good charge carrier transport performance.…”
Section: Introductionmentioning
confidence: 99%